Comparison of antibacterial and cytotoxic activities of phytosynthesized ZnONPs by leaves extract of Daphne mucronata at different salt sources. (15th October 2021) - Aljelehawy, Qassim; Karimi, Naser; Alavi, Mehran
ABSTRACT: In this research, an aqueous extract of Daphne mucronata leaves with different salt sources including Zn(NO3 )2 and ZnSO4 solutions were used to synthesize ZnO-N and ZnO-S NPs, respectively. The physicochemical, antibacterial, antioxidant, and cytotoxic properties of these NPs were also surveyed. SEM and TEM images confirmed that the ZnO-N and ZnO-S NPs were polydispersed with spherical and plate shape and average diameters of 129 ± 45.49 nm and 87 ± 31.61 nm, respectively. The minimum bactericidal concentration (MBC) values for both NPs against bacterial strains were 2 mg/ml. The biofilm growth in biofilm producer strains was completely inhibited at minimum inhibitory concentration (MIC). The IC50 values for ZnO-N and ZnO-S NPs were calculated as 1.946 mg/ml and 0.369 mg/ml, respectively. Finally, due to the antioxidant, antimicrobial, and cytotoxic properties of zinc oxide NPs, green synthesis of ZnONPs using D. mucronata can improve their applications in a wide range of clinical areas.